MicroRNAs in the regulation of Th17/Treg homeostasis and their potential role in uveitis - Tang, Fen; Zhou, Zhou; Huang, Kongqian; Deng, Wen; Lin, Jiali; Chen, Ruoyun; Li, Min; Xu, Fan (Frontiers in Genetics, 2022)
Th17 and regulatory T cell (Treg) play crucial roles in the pathogenesis of autoimmune diseases. Th17/Treg homeostasis is critically involved in maintaining immune balance. Disturbed Th17/Treg homeostasis contributes to the progression of autoimmune diseases. MicroRNAs (miRNAs) have emerged as a new vital factor in regulation of disturbed Th17/Treg homeostasis. To better understand the epigenetic mechanisms of miRNAs in regulating Treg/Th17 homeostasis, we included and evaluated 97 articles about the autoimmune diseases, and found that miRNAs were involved in the regulation of Treg/Th17 homeostasis from several aspects positively or negatively, including Tregs differentiation and development, Tregs induction, Treg stability, Th17 differentiation, and Tregs function. Uveitis is one of the ocular autoimmune diseases, which is also characterized with Th17/Treg imbalance. However, our understanding of the miRNAs in the pathogenesis of uveitis is unelusive and not well studied. In this review, we further summarized miRNAs found to be involved in autoimmune uveitis and their potential role in the regulation of Th17/Treg homeostasis.